Is co2 laser Hemorrhoidectomy superior to conventional open Hemorrhoidectomy? - Sultan, Sa`ad H; Kamal, Zuhair B; Al-Atroshi, Mohammad A; Al-Fayadh, Raysan; Hussein, Wisam A (AL-Kindy College Medical Journal, 2010)
Background: Hemorrhoids are one of the most common surgical conditions .Conventional haemorrhoidectomy was the traditional operation for the treatment of hemorrhoids. Other modalities of treatment had been used as an alternative operations including CO2 laser haemorrhoidectomy. Objectives: To determine the outcome of treatment of hemorrhoids by using CO2 laser haemorrhoidectomy and its advantages over conventional surgery Methods: This is a retrospective comparative interventional study of 1024 case of third degree haemorhoids selected out of 1300 case of hemorrhoids of different degrees, admitted to ALKINDY, ALYERMOUK teaching hospitals and ABD ALMAGEED private hospital, from May 1998 to July 2002,they were treated by CO2 laser haemorrhoidectomy and conventional surgery. They are divided into 2 groups randomly, 512 cases treated by CO2 laser (group A), 512 cases treated by conventional surgery (group B). Both groups were studied regarding operative time, hospital stay, healing time, post operative complications and cost effectiveness. Results: In GROUP A, the operative time ranged from 10 to 20 minutes with an average of 13 minutes. The hospital stay ranged from 4 to 12 hours with a mean time of 10 hours as all cases were treated as day cases. Post operative pain was minimal in 50% of patients and required simple analgesia for treatment while 50% had no pain. Bleeding occurred in less than 1% of cases, anal stenosis 3.3%, Infection recorded in 0.58% of patients.In GROUP B, The operative time ranged from 15 to 25 minutes with an average time of (19) minutes, hospital stay ranged from 24 to 48 hours with a mean time of 28 hours .Post operative pain recorded in all the patients (100%) and required narcotic analgesia for treatment, 25 patients (4.8%) had varying degrees of bleeding, 40 patients (7.8%) had infection, 25 patients (4.8%) had anal stenosis.In group A due to shorter hospital stay, earlier healing of wounds, earlier return to work which was within 7 to 10 days, the surgical treatment proved to be cost effective